CONSTITUTIONAL REFERENDUM AND JUDICIAL REFORM IN SERBIA (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
Abstract: The process of constitutional revision can be viewed from two points: the first, which refers to the elements of the constitutional change procedure, and the second, which requires a review of the subject of constitutional revision contained in the Act on the Revision of the Constitution. This paper discusses the legitimation of the Act amending the Constitution, as well as new constitutional solutions that change the provisions on the election of judges and public prosecutors, and the provisions on judicial councils in the Republic of Serbia.
Keywords: Constitution of the Republic of Serbia. Constitutional Revision. Judicial Reform.